Smart Governance Policy: An Overview of The Local Government Performance - Riska Sarofah (Jurnal Ilmiah Wahana Bhakti Praja, 2023)
One of the challenges in digital transformation is building a comprehensive digital ecosystem. This article aims to analyze smart governance policies in improving government efficiency in Indonesia. The number of applications cannot be used as a benchmark in determining the performance of governance implementation. This article uses a qualitative research method with the approach of a systematic literature review. The results of the study found that smart governance policies are oriented to 4 indicators, including community participation, effective governance, public and social services, and political perspectives and strategies. This policy will be successful if implemented collaboratively and integratively. The novelty of the research is in the exploration of policies in local government because until now smart governance policies have not been fully implemented, especially in regions that do not have a clear vision strategy. This research also develops various smart governance policy challenges including digital technology infrastructure, organization, policy reform, and collaborative work development.